Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Terhadap Hasil Belajar Siswa Terutama untuk Siswa Kelas V-B di UPTD SDN Mlajah 2 Bangkalan - Fitrih, Dwi Rosita; Maula, Qurrotu Inayatil (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the significant effect on student learning outcomes in Pancasila Education subjects for grade V using the Teams Games Tournament (TGT) cooperative learning model. This study is a quantitative study with the type of Quasi Experimental Design and uses a Nonequivalent Control Group research design wich means that the control sample is not selected randomly. The sample used in this study was 41 students in grade V-B as the experimental class and 40 students in grade V-A as the control class. Data collection techniques used were tests and observations. The trial of the thest instrument used validity, reliability, difficulty level, and discrimonatory power tests. Hypothesis testing used the Independent Sample T-Test. Based on the result of the Independent Sample T-Test data analysis on the posttest, a significance value of 0,000 was obtained, in accordance with the criteria that if the 2-tailed significance value < 0,05, then Ho is rejected and Ha is accepted. The result of the hypothesis test indicate that there is a significant diffirence in the application of the Teams Games Tournament (TGT) learning model on student learning outcomes in Pancasila Education subjects for grade V.